Extra Ecclesiam Nulla Salus : Sebuah Tinjauan Teologis Doktrin Keselamatan Dari Perspektif Teologi John Wesley Terhadap Kristen Progresif - Adi, Didit Yuliantono; Sanyoto, Kroliyus Puji; Wibowo, Adi Prasetyo (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Currently, it is going viral on social media about deviant teachings from people who claim to be progressive Christians. The salvation taught by progressive Christians is contrary to the concept of salvation in the Christian faith. The Christian concept of salvation from ancient times to the present remains the same, never changing that salvation can only be obtained in Jesus Christ. The Bible very clearly says that He is the way, the truth, and the life; no one can come to the Father except through Him. In this research, the author used a descriptive qualitative research method with the aim of looking for Biblical evidence and literature regarding the correct concept of salvation regarding Christianity. The findings from the presentation of this topic reveal that the salvation taught by Progressive Christians is heretical because, firstly, it rejects Jesus as the only God and Savior of mankind; secondly, it upholds pluralism that in all religions there must be salvation; and thirdly, it teaches that salvation can be obtained by doing deeds. well, and fourthly rejecting the Bible as the ultimate authority for Christians.